Priority Handling of Teurebeh Irrigation Assets, Aceh Besar District, Aceh Province - Azmeri*, Azmeri; Ar-rahman, Beryl Choliq; Jemi, Faris Zahran; Refika, Cut Dwi; Shaskia, Nina (Aceh International Journal of Science and Technology, 2023)
Teurebeh Irrigation scheme is one of the promising irrigation areas in Aceh Besar District, Aceh Province. It is also one of the buffers in the agricultural sector, covering 750 hectares of agricultural area. However, the construction has shrunk over time, and the evaluation at the end of 2020 classified it as "Poor Performance and Requiring Attention." This study aims to determine the handling priority for the irrigation networks at the Teurebeh Irrigation scheme. Data on irrigation network inventory was used as input. The determination of handling priority was conducted using the MannWhitney method. The ranking for determining the priority of irrigation assets is based on the condition and function of the irrigation assets. ArcGIS and Google Earth software were used to determine the condition and handling of all assets. The results show that the handling priority levels are between the primary and secondary channels. The priority for handling irrigation structure in the secondary channel is for two tapping structures, and one divider structure are ranked 1 to 3. They must be fixed immediately as severe to moderately damaged conditions are not functioning correctly. Furthermore, the priority for handling irrigation structure in the primary channel is for two bridges, and one divider structure are within priority 1 to 3. The Mann-Whitney test on the proposed hypothesis comparing the urgency level between the two channels is insignificant, indicating no significant difference between the handling of primary and secondary channels, as both have similar conditions and functions. The results are expected to contribute to decision-making at the Irrigation Department in designing proposals for renovating irrigation networks.